Benefits of nutritional yeast for children on vegan diet - Justyna Justyna; Konrad Gładysz; Olga Żuchnik; Olgierd Król; Piotr Kwiatkowski; Beata Kuczyńska; Magdalena Czelej; Aleksander Kłos; Krzysztof Gieroba; Marcin Szydłowski (Kazimierz Wielki University, 2022)
Introduction: Nutritional yeast are a food product that can be fortified with valuable components. They are a product suitable for introducing into the diet of vegan children due to their friendly form, good taste and relatively low cost. Aim of the study: Summarize current knowledge on the benefits of introducing nutritional yeast into children's diets as supplementation for deficiencies in a vegan diet. Demonstrate the positive impact of the product on the health of the body. Methods and materials: : A review of the literature available in the PubMed database and Google Scholar, the following keywords were used: "nutritional yeast", "vegan diet in children", "nutritional yeast impact on health". Results: Introducing nutritional yeast into the diet of a child restricting animal products has measurable benefits. It reduces the risk of deficiencies such as deficiency of vitamin B12, zinc, protein and the following disease symptoms. Conclusion: The constantly growing number of infants and older children on vegan diets is a challenge for modern pediatrics, but also an opportunity to find new products that meet the high nutritional requirements of children during the developmental period. Nutritional yeast can be considered such a product thanks to their richness in nutrients that meat products contain but are not found in plant based foods. Nutritional yeast, however, cannot be a reason to completely abandon other sources of vitamin B12 supplementation.